2009
DOI: 10.1073/pnas.0909411106
|View full text |Cite
|
Sign up to set email alerts
|

Dual blockade of FAAH and MAGL identifies behavioral processes regulated by endocannabinoid crosstalk in vivo

Abstract: ⌬ 9 -Tetrahydrocannabinol (THC), the psychoactive component of marijuana, and other direct cannabinoid receptor (CB1) agonists produce a number of neurobehavioral effects in mammals that range from the beneficial (analgesia) to the untoward (abuse potential). Why, however, this full spectrum of activities is not observed upon pharmacological inhibition or genetic deletion of either fatty acid amide hydrolase (FAAH) or monoacylglycerol lipase (MAGL), enzymes that regulate the two major endocannabinoids anandami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
424
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(463 citation statements)
references
References 42 publications
35
424
2
2
Order By: Relevance
“…Indeed, URB597 administration was effective in decreasing the mechanical hyperalgesia and the anxiety-like behavior induced by CUS in mice even in more challenging anxiety tests (EPM), whereas JZL184, consistent with previous reports (Sciolino et al, 2011;Sumislawski et al, 2011), was not. Interestingly, simultaneous inhibition of FAAH and MAGL (combo), known to induce analgesia in mice (Long et al, 2009b), did not elicit further alleviation of the CUSinduced anxiety and hyperalgesia as compared with individual drug administration. Notably, in our experiments, neither URB597, JZL184, nor combo treatment reversed the depression-like behavior observed in CUS mice.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, URB597 administration was effective in decreasing the mechanical hyperalgesia and the anxiety-like behavior induced by CUS in mice even in more challenging anxiety tests (EPM), whereas JZL184, consistent with previous reports (Sciolino et al, 2011;Sumislawski et al, 2011), was not. Interestingly, simultaneous inhibition of FAAH and MAGL (combo), known to induce analgesia in mice (Long et al, 2009b), did not elicit further alleviation of the CUSinduced anxiety and hyperalgesia as compared with individual drug administration. Notably, in our experiments, neither URB597, JZL184, nor combo treatment reversed the depression-like behavior observed in CUS mice.…”
Section: Discussionmentioning
confidence: 89%
“…URB597 treatment had no significant effects in control mice (Figure 2e and f). To investigate whether the anxiety-and depression-like behaviors induced by JZL184 and combo in control mice resulted from drug-induced cannabimimetic effects, as reported for high doses of JZL184 and combined fatty acid amide hydrolase (FAAH)/monoacylglycerol lipase (MAGL) inhibitors (Long et al, 2009b;Wise et al, 2012), we tested mice in the tetrad behavioral paradigm. We found that temperature, catalepsy (bar test), and locomotion (EPM and open field tests) were not changed in drug-treated mice as compared with vehicle-treated animals (data not shown).…”
Section: Anxiety-and Depression-like Behaviorsmentioning
confidence: 99%
“…It is proposed that AM6701 exerts a synergistic action on the endocannabinoid system by acting on AEA and 2-AG responses to protect against seizures. According to Long et al [66], dual augmentation of the AEA and 2-AG signaling pathways allows these 2 lipid transmitters to engage in extensive crosstalk. A critical balance between AEA and 2-AG levels, controlled by endocannabinoid synthesizing and metabolizing enzymes, may therefore be important for normal physiological processes, as well as to promote repair after pathological events [1,45,48,67].…”
Section: Discussionmentioning
confidence: 99%
“…Brains were sliced (50 mm) at À 10 1C to confirm probe placement into the VTA, and the alternate side was sliced (500 mm) and punched for the VTA (Supplementary Methods). Brain punches were processed and analyzed for fatty acid amide hydrolase (FAAH) activity using previously published methodology (Long et al, 2009). VTA punches were homogenized in icecold PBS, and FAAH activity determined by incubating 100 ml of protein homogenate (0.5 mg/ml, PBS) with 100 mM d 8 -AEA in glass vials (37 1C for 30 min).…”
Section: Effect Of Nicotine Exposure On Faah Activitymentioning
confidence: 99%